Patterns of Cranial Metastases in Primary Lung Cancer: A Study from a Tertiary Cancer Center in Northwestern India - Mohata, Shweta; Goswami, Vishal; Sharma, Neeti; Harsh, Kamlesh Kumar; Karadiya, Kirti (Asian Pacific Journal of Cancer Care, 2025)
Background: Brain metastases (BM) are the most common intracranial neoplasms in adults and are a frequently occur in the course of lung carcinoma. This study aims to assess the possible correlation between the site and histology of lung cancer and the likelihood of metastatic disease spreading to brain. Materials and Methods: A retrospective study was conducted at our institute over a period of three years (January 2021 to December 2023) to evaluate the relationship between the site and histology of primary lung malignancy and the incidence of BM. Patients were categorized into two groups: those with brain metastases at the time of diagnosis (whether solitary or multiple) and those who developed BM during treatment and follow-up. The variables analysed included the site and pathological type of primary tumour in correlation with the location and frequency of cranial metastases. Results: A total of 496 patients with primary lung cancer were enrolled into the studied. Out of which 94.35% (n=468) patients had Non-Small Cell Lung Carcinoma (NSCLC), while 5.65% (n=28) patients had Small Cell Lung Carcinoma (SCLC). 97 patients (19.56%) had BM, out of which 89.69% (n=87) patients having NSCLC and 10.31% (n=10) patients having SCLC histology. Among patients with unilateral primary tumour on the left side, BM was observed in 65.98% (n=64) patients, of which 90.63% (n=58) patients had NSCLC and 9.37% (n=6) patients SCLC respectively. In contrast, for patient with primary tumour on the right side, BM occurred in 25.77% (n=25) patients with 88% (n=22) patients having NSCLC and 12% (n=3) patients SCLC respectively. Among patients with bilateral lung cancer, BM was observed in 8.25% (n=8) patients of which 75% (n=6) patients having NSCLC and 25% (n=2) patients having SCLC respectively. Predictive factors of brain metastases included small-cell lung cancer, followed by left-side adenocarcinoma. Conclusion: This study highlights the high incidence of BM in patients with primary left-side NSCLC. Overall, small cell carcinoma, followed by adenocarcinoma is more frequently associated with symptomatic BM. However, the underlying cause of the correlation between frequency of BM and primary tumour site remains unclear and requires further investigation to establish a causal relationship.